Atender o cuidar. Un problema contextual por discernir en la práctica profesional de enfermería. - Delís, Félix Kindelán (MEDISAN, 2013)
The object of a science comprises phenomena either from nature as from social life; it includes properties from mental activity of men as a result of the imagination, and it involves functions of the abstract thought, such as: concept, judgment and reasoning. It doesn't constitute a certainty given forever, it is transformable; it preserves certain degree of stability and it designs the essence of the cultural actor's directional scientific performance, but if in science terminological bilaterality exists, then there will be disintegration of the essence of its emergence and development. The basic logical way of emergence of knowledge will be diffuse, and to distinguish the singularity of the knowledge to which it joints will create dispersion in thinking. For such reasons this work was carried out to decipher the existent contextual problem between the concepts to care/to assist which guide the nursing professional practice in Cuba.